Sulfur foam full-quantification recovery treatment system and method based on integrated reaction tower
By integrating the oxidation-catalysis design of the reaction tower with Fe-Cu bimetallic catalyst, the problems of heat loss, deactivation of active intermediates and scaling during the resource recovery of sulfur foam were solved, achieving efficient and full-quantity recovery of sulfur and nitrogen elements and stable equipment operation.
Patent Information
- Application Number
- CN202511760312.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-01-13
AI Technical Summary
The existing sulfur foam resource utilization route suffers from serious heat loss, deactivation of active intermediates, frequent equipment scaling, and incomplete resource utilization. This is mainly due to the fragmentation of the oxidation and catalytic conversion processes, resulting in uneven slurry distribution and low energy utilization efficiency.
An integrated reaction tower is adopted, combining an oxidation-catalysis integrated design, including a forced oxidation zone, an adiabatic guiding liquid distribution zone, and a fixed-bed catalytic conversion zone. It uses an Fe-Cu bimetallic oxide catalyst and achieves uniform distribution and efficient conversion of the slurry through an annular V-groove guiding liquid distributor.
It achieves efficient and full-quantity recovery of sulfur and nitrogen elements, significantly reduces system energy consumption, extends the continuous operation cycle of equipment, reduces scaling, and improves conversion rate and resource utilization.
Smart Images

Figure CN121314477A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hazardous waste resource utilization technology in the coking industry, and specifically proposes a sulfur foam full-scale recovery and treatment system and method based on an integrated reaction tower. Background Technology
[0002] When coking plants use ammonia-based wet oxidation desulfurization (HPF, PDS, etc.) to remove H2S and HCN from coke oven gas, they generate a large amount of sulfur foam. This substance has been listed in the National Hazardous Waste List (HW18), and its main components are elemental sulfur, ammonium sulfate, ammonium thiosulfate, ammonium thiocyanate, and water. Improper disposal of sulfur foam will cause serious environmental pollution; if it is directly reused, the accumulated salts will inhibit desulfurization efficiency, creating a sharp conflict between production and environmental protection.
[0003] The current mainstream route for sulfur foam resource utilization in the industry is "solid-liquid separation - independent oxidation tower - independent catalytic conversion tower - sulfur slurry incineration to produce acid", with representative technologies such as CN114602299A. Although this type of technology has been industrialized, the core ammonium salt conversion process suffers from several insurmountable common defects: First, heat loss is severe. When the high-temperature oxidation slurry (130–150℃, 0.4–0.6MPa) is transported through pipelines to the independent catalytic conversion tower, heat loss reaches 18–25%, requiring additional steam to maintain the reaction temperature, resulting in high energy consumption. Second, active intermediates are deactivated. Highly active intermediates such as peroxide complexes and superoxide radicals generated during the oxidation stage have extremely short half-lives (<45s) and are almost completely deactivated during pipeline transportation and heat exchange, making them unable to participate in the subsequent catalytic conversion of ammonium thiocyanate and limiting conversion efficiency. Third, equipment scaling is frequent. Temperature and pressure fluctuations cause dissolved elemental sulfur to re-precipitate, resulting in severe scaling of pipelines, distributors, and catalyst beds. The continuous operation cycle of the unit is only 280–380 hours, leading to high maintenance costs. Fourth, resource utilization is incomplete. Affected by the above factors, the long-term conversion rate of ammonium thiocyanate is difficult to stably exceed 98.5%, with nitrogen loss of 2–4%, and fluctuations in product yield and quality.
[0004] Further analysis reveals that the core bottleneck of existing technologies lies in the "separation of the oxidation and catalytic conversion processes." Furthermore, traditional flow distribution structures are mostly single conical or flat plate shapes, which cannot solve the problem of "wall-adhering flow" of the slurry after oxidation. This leads to uneven slurry distribution and "channeling" in the catalyst bed, further exacerbating the problems of low conversion efficiency and severe scaling. Therefore, there is an urgent need in this field for a novel technical solution that can structurally eliminate process separation, achieve uniform slurry distribution, efficient energy utilization, and in-situ retention of active intermediates, thus completely resolving the pain points of existing technologies. Summary of the Invention
[0005] In view of this, the present invention proposes a sulfur foam full-quantity recovery and treatment system and method based on an integrated reaction tower, which aims to completely solve the problems of heat loss, deactivation of active intermediates and scaling caused by external material transportation in the existing technology, and realize the efficient full-quantity recovery of sulfur and nitrogen elements in sulfur foam.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a sulfur foam full-scale recovery and treatment system based on an integrated reaction tower. Its core is an integrated oxidation-catalysis reaction tower, which is a single vertical pressure vessel. From top to bottom, it includes a forced oxidation zone, an adiabatic flow distribution zone, and a fixed bed catalytic conversion zone. The forced oxidation zone and the fixed bed catalytic conversion zone are connected only through the adiabatic flow distribution zone, without any external pipes.
[0007] The forced oxidation zone is located at the top of the reaction tower, accounting for 40-45% of the total height of the tower. A slurry inlet is provided at the top, and an umbrella-shaped pre-distributor is installed below the inlet. Aeration plates are laid horizontally at the bottom, with aeration pore diameter of 0.5-2μm. A 10-15mm annular material drop gap is reserved between the outer ring of the aeration plate and the inner wall of the reaction tower, serving as the only falling channel for the oxidized slurry. The forced oxidation zone controls the temperature at 130-150℃ and the pressure at 0.4-0.6MPa through the steam jacket on the outer wall of the tower, and controls the excess air coefficient at 35-40%.
[0008] The insulated flow distribution zone is located between the forced oxidation zone and the fixed-bed catalytic conversion zone, accounting for 10-15% of the total height of the tower. The outer wall of the tower is wrapped with a 50-80mm thick aluminum silicate fiber insulation layer. The core component is 3-5 layers of coaxially arranged annular V-shaped groove flow distributors. The axes of all annular V-shaped grooves are completely coincident with the axis of the tower, forming a stepped distribution with a large diameter at the top and a small diameter at the bottom. The cross-section of each annular V-shaped groove is V-shaped with an included angle of 60-75° and a groove depth of 8-100mm. The tank is 15mm thick and made of 316L stainless steel with polished walls. The diameter of the uppermost annular V-shaped tank is 90-95% of the tower diameter. The diameter of adjacent annular V-shaped tanks decreases by 15-20% from top to bottom, and the projection of the lower annular V-shaped tank opening completely covers the projection of the upper annular V-shaped tank bottom. The vertical spacing between adjacent annular V-shaped tanks is 200-300mm to ensure that the residence time of the slurry in this area is ≤30s and the temperature drop is ≤5℃.
[0009] The fixed-bed catalytic conversion zone is located at the bottom of the reaction tower, accounting for 40-45% of the total height of the tower. A wire mesh filter layer (50-100 μm pore size) is installed at the top, and the bottom is filled with Fe-Cu bimetallic oxide catalyst supported on a hierarchical porous activated carbon support. The bed height is 4.5-5.0 m. The mesopore (2-50 nm) pore volume of the hierarchical porous activated carbon support accounts for 63-78%, and the macropore (>50 nm) pore volume accounts for 15-25%. In the Fe-Cu bimetallic oxide, the atomic molar ratio of Cu to Fe, Cu / (Fe+Cu), is 0.23-0.37, and it exists in the form of a coexistence of CuFe2O4 spinel phase and CuO phase. The catalytic conversion zone utilizes the residual heat from the oxidation zone to maintain a temperature of 50-80℃ and a pressure of 0.02-0.06 MPa (slightly positive). A porous support plate and a conversion liquid outlet are provided at the bottom, and a catalyst loading and unloading port is provided on the side.
[0010] This invention also provides a method for the full-scale recovery and treatment of sulfur foam based on an integrated reaction tower. Using the aforementioned system, sulfur foam is separated and concentrated by super centrifugation to obtain a concentrated slurry with a total salt concentration of 480–520 g / L. The concentrated slurry is added from the top of the forced oxidation zone, initially dispersed by an umbrella-shaped pre-distributor, and then fully contacted with micron-sized bubbles generated by the aeration plate under high temperature and pressure conditions. Ammonium thiosulfate is forcibly oxidized to ammonium sulfate, producing a highly active intermediate. The oxidized slurry falls into the adiabatic distribution zone through an annular material drop gap, and is gradually distributed towards the center of the tower through 3–5 layers of annular V-shaped grooves, forming a uniform thin-layer liquid flow covering the entire cross-section of the tower. The uniformly distributed slurry is filtered through a wire mesh filter layer and then permeates into the fixed-bed catalytic conversion zone, where ammonium thiocyanate is deeply converted to ammonium sulfate under the action of an Fe-Cu bimetallic catalyst. After solid-liquid separation, the conversion liquid yields ammonium sulfate product. The solid sulfur-containing substances are combined with the centrifuged concentrated slurry and sent to an incinerator for acid production. The exhaust gas is treated and discharged in compliance with standards.
[0011] The present invention has the following advantages over the prior art: This invention, through the innovative combination of an integrated oxidation-catalysis tower and an annular V-shaped channel liquid distribution zone, coupled with a dedicated Fe-Cu bimetallic catalyst, fundamentally solves the core pain points of traditional separate tower processes. Compared to existing technologies, it not only completely eliminates heat loss and active intermediate deactivation caused by external material transportation, achieving efficient energy recovery and utilization and significantly reducing system energy consumption, but also effectively avoids slurry wall-adhering flow and channeling phenomena through the precise liquid distribution design of the stepped annular V-shaped channel, greatly improving the catalyst bed utilization rate and ensuring more thorough conversion and comprehensive recovery of sulfur and nitrogen elements. Simultaneously, the synergistic effect of uniform liquid distribution and the dedicated catalyst reduces localized material deposition and elemental sulfur re-precipitation, completely alleviating equipment scaling problems, significantly extending the system's continuous operation cycle, and reducing maintenance costs. The entire system structure is compact and rationally designed, forming a closed-loop environmentally friendly process that meets the actual needs of industrial promotion and enables the full-scale resource utilization of hazardous waste. Its technical effect is not a simple improvement of a single structure, but rather an inseparable synergistic effect of multiple core technical features, possessing outstanding substantial progress and irreplaceability. Attached Figure Description
[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0013] Figure 1 This is a main cross-sectional view of the integrated reaction tower of the present invention.
[0014] In the figure: 1-tower body, 10-slurry inlet, 11-forced oxidation zone, 12-insulated flow distribution zone, 13-fixed bed catalytic conversion zone, 14-conversion liquid outlet, 2-umbrella-shaped pre-distributor, 3-aeration plate, 4-annular V-groove, 5-wire mesh, 6-bimetallic catalyst, 7-ceramic porous support plate. Detailed Implementation
[0015] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0016] Raw materials and general equipment Sulfur foam raw material: Sulfur foam produced by the HPF process in a coking plant, with a solid content of 10.5 wt%, including 8.2% ammonium thiosulfate, 5.1% ammonium thiocyanate, 10.2% elemental sulfur, 15.3% ammonium sulfate, and 50.7% moisture and other components; General equipment: super centrifuge, triple-effect falling film concentrator, plate and frame filter press, incinerator, gas chromatograph, differential pressure transmitter.
[0017] Example 1 1. Catalyst preparation steps Step 1: Take coal-based columnar activated carbon (Φ1.5mm), reflux it with 15wt% nitric acid solution at 100℃ for 4 hours, stirring every 30 minutes during the process. After activation, wash repeatedly with deionized water until the washing solution is neutral, dry in an oven at 110℃ for 12 hours, and then place it in a steam activation furnace at 1200℃ for 90 minutes to obtain a hierarchical porous activated carbon carrier. Analysis showed that its pore volume ratio was 71% for mesopores (2-50nm), 19% for macropores (>50nm), and the total pore volume was 1.18 cm³. 3 / g; Step 2: Weigh ferric nitrate (Fe(NO3)3·9H2O) and copper nitrate (Cu(NO3)2·3H2O) according to the Cu / (Fe+Cu) atomic molar ratio of 0.30, and prepare a mixed aqueous solution with a total concentration of 0.5 mol / L using deionized water. Spray the mixed solution evenly onto the carrier obtained in Step 1 using the equal volume impregnation method to ensure that the carrier is completely wetted. Allow it to stand at room temperature for 12 hours for adsorption. Step 3: The impregnated support was placed in a muffle furnace and calcined at 350°C in air for 2 hours at a heating rate of 5°C / min. After naturally cooling to room temperature, it was transferred to a tube furnace and calcined at 550°C in nitrogen atmosphere for 3 hours at a nitrogen flow rate of 50 mL / min. After calcination, it was cooled to room temperature to obtain a Fe-Cu bimetallic catalyst with a loading of 10.8 wt%. XRD analysis showed that it contained CuFe2O4 spinel phase and CuO phase.
[0018] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Overall tower structure: a single vertical pressure vessel, made of 316L stainless steel, with a total height of 12m, an inner diameter of 1.8m, a wall thickness of 16mm, and the tower axis is perpendicular to the ground and fixed to the equipment foundation by the bottom support. Forced oxidation zone: Located at the top of the tower, 5m high (accounting for 41.7% of the total height), with a DN100 slurry inlet at the center of the top. An umbrella-shaped pre-distributor is installed 100mm below the inlet, with a diameter of 1.44m (80% of the tower diameter) and a 50° angle. Made of 316L stainless steel, it is welded to the inner wall of the tower via three symmetrically distributed supports. At the bottom of the forced oxidation zone, aeration plates are laid horizontally, with a diameter of 1.62m (covering 90% of the tower cross-section) and 1μm aeration holes. The aeration plates have an annular air chamber connected to an external air compressor via a DN50 pipe, with a flow regulating valve and pressure gauge installed on the pipe. A 12mm annular material drop gap is reserved between the outer ring of the aeration plates and the inner wall of the tower, with the gap evenly distributed circumferentially and unobstructed. A steam jacket, 50mm thick, is wrapped around the outer wall of the tower corresponding to the forced oxidation zone, with temperature controlled by a steam valve. Insulated flow distribution zone: Located below the forced oxidation zone, 1.5m high (accounting for 12.5% of the total height), the outer wall of the tower is wrapped with an 80mm thick aluminum silicate fiber insulation layer, and the insulation layer is covered with a sheet metal protective layer; inside, there are 4 layers of coaxially arranged annular V-shaped groove flow distribution devices, and the axis of all annular V-shaped grooves is completely coincident with the axis of the tower body; each annular V-shaped groove is made of 316L stainless steel, the groove wall is polished (surface roughness Ra≤0.8μm), the cross-sectional angle is 65°, and the groove depth is 12mm; from top to bottom... The first layer of annular V-grooves has a diameter of 1.71m (95% of the tower diameter), the second layer has 1.45m (decreasing by 18%), the third layer has 1.23m (decreasing by 15%), and the fourth layer has 1.04m (decreasing by 16%). The projection of the groove opening of the lower layer of annular V-grooves completely covers the projection of the bottom of the upper layer of annular V-grooves. The vertical spacing between two adjacent layers of annular V-grooves is 250mm. Each layer of annular V-grooves is welded and fixed to the inner wall of the tower by four symmetrically distributed supports. The height of the supports is adjustable to ensure that the annular V-grooves are horizontal. Fixed-bed catalytic conversion zone: Located below the adiabatic flow distribution zone, with a height of 5.5m (accounting for 45.8% of the total height), the top is equipped with a wire mesh filter layer with a pore size of 80μm. The wire mesh is made of 316L stainless steel and is fixed to the inner wall of the tower via flanges. Below the filter layer, the Fe-Cu bimetallic catalyst prepared in step 1 is filled, with a bed height of 4.8m. The catalyst particles are evenly distributed without gaps. At the bottom of the bed, there is a ceramic porous support plate with a thickness of 50mm and a pore size of 0.8mm, which is fixed to the inner wall of the tower via supports. A DN200 catalyst loading and unloading port is opened on the lower side of the catalytic conversion zone and sealed by a blind flange. A DN150 conversion liquid outlet is opened in the center of the bottom of the tower and connected to the feed pipe of the plate and frame filter press.
[0019] 3. System Operation Steps Step 1: After the sulfur foam is pumped into the sulfur foam tank for homogenization and buffering for 2 hours, it is sent to a super centrifuge. The speed is set to 1700 r / min and centrifuged for 20 minutes to obtain clear liquid and concentrated slurry. The clear liquid is sent to the clear liquid tank, of which 65% is returned to the coking desulfurization system for recycling through pipeline, and 35% is sent to the triple-effect falling film thickener through centrifugal pump. The steam pressure of the thickener is controlled at 0.3 MPa to concentrate the clear liquid to a total salt concentration of 505 g / L. The condensate generated during the thickening process is returned to the clear liquid tank. Step 2: The concentrated slurry is pumped through a metering pump at a rate of 2.5m... 3 A flow rate of / h is fed in from the slurry inlet at the top of the integrated reaction tower. After being initially dispersed by the umbrella-shaped pre-distributor, it falls into the liquid phase body of the forced oxidation zone. The steam valve of the steam jacket is opened to control the temperature of the forced oxidation zone at 135℃. Compressed air is introduced into the aeration plate through the air compressor. The air flow rate is adjusted to maintain the excess air coefficient at 38% and the system pressure is stabilized at 0.48MPa. Step 3: After the oxidation reaction is completed, the slurry, under the action of gravity and pressure difference, falls through the annular material drop gap at the bottom of the forced oxidation zone into the first layer of the annular V-shaped groove in the adiabatic guiding liquid distribution zone. It flows along the two sides of the groove wall towards the bottom of the groove, overflows evenly, and falls into the second layer of V-shaped groove. This even distribution process is repeated. After being guided by 4 layers of V-shaped grooves, a uniform thin layer of liquid flow covering the entire cross-section of the tower is formed. During the entire guiding process, the residence time of the slurry in the adiabatic guiding liquid distribution zone is about 25 seconds, and the temperature drops from 135℃ to 131℃, a temperature drop of 4℃. Step 4: The uniformly distributed slurry is filtered through the wire mesh filter layer at the top of the fixed bed catalytic conversion zone and then vertically penetrates into the catalyst bed. The temperature of the catalytic conversion zone is controlled at 65℃ and the micro-positive pressure is 0.03MPa. The slurry stays in the bed for about 100 minutes. Under the action of the Fe-Cu bimetallic catalyst, ammonium thiocyanate is deeply converted into ammonium sulfate. Step 5: The conversion liquid flows out from the conversion liquid outlet at the bottom of the integrated reaction tower and is sent to the plate and frame filter press through the pipeline. The filtration pressure is set to 0.6MPa for solid-liquid separation. The filtrate is a high-purity ammonium sulfate solution and is sent to the ammonium sulfate storage tank as a product. The filter residue is mainly elemental sulfur and is sent to the concentrated sulfur foam buffer tank through the pipeline and combined with the concentrated slurry obtained from the super centrifuge. Step 6: The mixed slurry in the concentrated sulfur foam buffer tank is pumped into the incinerator and burned at 1050℃ under slight negative pressure (-5kPa), converting elemental sulfur into SO2 flue gas. After being purified by a high-efficiency humidification tower, a packed cooling tower, and a two-stage electrostatic precipitator, the flue gas is dried with 93% concentrated sulfuric acid and then converted into 98% industrial sulfuric acid through a "two-conversion, two-absorption" process. The tail gas is treated by a hydrogen peroxide tail absorption system and discharged in compliance with standards. The dilute acid produced is returned to the system as makeup water.
[0020] Example 2 1. Catalyst preparation steps Step 1: Take coal-based columnar activated carbon (Φ1.5mm), reflux it with 15wt% nitric acid solution at 100℃ for 4 hours, wash it with water until neutral, dry it at 110℃ for 12 hours, and then activate it with steam at 1200℃ for 90 minutes to obtain a hierarchical porous activated carbon carrier. Analysis showed that the pore volume of mesopores (2-50nm) accounted for 63%, the pore volume of macropores (>50nm) accounted for 25%, and the total pore volume was 1.05cm³. 3 / g; Step 2: Weigh out ferric nitrate and copper nitrate according to the Cu / (Fe+Cu) atomic molar ratio of 0.23, prepare a mixed aqueous solution with a total concentration of 0.5 mol / L, and impregnate it with an equal volume of the carrier obtained in Step 1, and let it stand at room temperature for 12 hours. Step 3: Calcination at 350℃ in air atmosphere for 2 hours, followed by calcination at 550℃ in nitrogen atmosphere for 3 hours, yielding a Fe-Cu bimetallic catalyst with a loading of 10.2wt%. XRD analysis showed that it contained CuFe2O4 spinel phase and CuO phase.
[0021] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Overall tower structure: total height 11m, inner diameter 1.8m, wall thickness 16mm; Forced oxidation zone: 4.4m high (accounting for 40% of the total height), umbrella-shaped pre-distributor with an umbrella surface angle of 45°, and a 10mm annular material drop gap reserved between the outer ring of the aeration plate and the tower wall; Insulated flow distribution zone: 1.1m high (10% of the total height), the outer wall of the tower is wrapped with a 50mm thick aluminum silicate fiber insulation layer; the interior is equipped with 3 layers of annular V-shaped groove flow distributors, with a cross-sectional angle of 60° and a groove depth of 8mm; from top to bottom, the diameter of the first layer of V-shaped grooves is 1.62m (90% of the tower diameter), the second layer is 1.38m (decreasing by 15%), and the third layer is 1.17m (decreasing by 15%); the vertical spacing between adjacent layers is 200mm; Fixed bed catalytic conversion zone: 5.5m in height (accounting for 50% of the total height), wire mesh filter layer with a pore size of 50μm, and catalyst bed height of 4.5m.
[0022] 3. System Operation Steps Step 1: The sulfur foam is separated by a super centrifuge (1500 r / min), and 35% of the clear liquid is sent to a concentration tower to concentrate to a total salt concentration of 480 g / L; Step 2: Concentrate the slurry at 2.0m 3 A flow rate of / h is fed into the integrated reaction tower, with a forced oxidation zone temperature of 130℃, a pressure of 0.4MPa, and an excess air coefficient of 35%; Step 3: The slurry is evenly distributed through three layers of annular V-shaped grooves. The temperature in the catalytic conversion zone is 50℃, the pressure is 0.02MPa, and the slurry residence time is 90 minutes. Step 4: The remaining steps are the same as in Example 1.
[0023] Example 3 1. Catalyst preparation steps Step 1: Take coal-based columnar activated carbon (Φ1.5mm), reflux with 15wt% nitric acid at 100℃ for 4 hours, wash with water until neutral, dry at 110℃ for 12 hours, and then activate with steam at 1200℃ for 110 minutes to obtain a hierarchical porous activated carbon carrier. The pore volume ratio is 78% for mesopores (2-50nm), 15% for macropores (>50nm), and the total pore volume is 1.25cm³. 3 / g; Step 2: Weigh out ferric nitrate and copper nitrate according to the Cu / (Fe+Cu) atomic molar ratio of 0.37, prepare a mixed aqueous solution with a total concentration of 0.5 mol / L, and impregnate it with an equal volume of the carrier obtained in Step 1, and let it stand at room temperature for 12 hours. Step 3: Calcination at 350℃ in air atmosphere for 2 hours, followed by calcination at 550℃ in nitrogen atmosphere for 3 hours, yielding an Fe-Cu bimetallic catalyst with a loading of 11.5wt%. XRD analysis showed that it contained CuFe2O4 spinel phase and CuO phase.
[0024] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Overall tower structure: total height 13m, inner diameter 1.8m, wall thickness 16mm; Forced oxidation zone: 5.85m high (accounting for 45% of the total height), umbrella-shaped pre-distributor with an umbrella surface angle of 60°, and a 15mm annular material drop gap reserved between the outer ring of the aeration plate and the tower wall; Insulated liquid distribution zone: 1.95m high (15% of the total height), with an 80mm thick aluminum silicate fiber insulation layer wrapped around the outer wall of the tower; internally equipped with 5 layers of annular V-shaped groove liquid distributors, with a cross-sectional angle of 75° and a groove depth of 15mm; from top to bottom, the diameter of the first layer of V-shaped grooves is 1.71m (95% of the tower diameter), the second layer is 1.37m (decreasing by 20%), the third layer is 1.10m (decreasing by 20%), the fourth layer is 0.88m (decreasing by 20%), and the fifth layer is 0.70m (decreasing by 20%); the vertical spacing between adjacent layers is 300mm; Fixed bed catalytic conversion zone: height 5.2m (accounting for 40% of the total height), wire mesh filter layer pore size 100μm, catalyst bed height 5.0m.
[0025] 3. System Operation Steps Step 1: The sulfur foam is separated by a super centrifuge (1800 r / min), and 35% of the clear liquid is sent to a concentration tower to concentrate to a total salt concentration of 520 g / L; Step 2: Concentrate the slurry at 3.0m 3 A flow rate of / h is fed into the integrated reaction tower, with a forced oxidation zone temperature of 150℃, a pressure of 0.6MPa, and an excess air coefficient of 40%; Step 3: The slurry is evenly distributed through 5 layers of annular V-shaped grooves. The temperature in the catalytic conversion zone is 80℃, the pressure is 0.06MPa, and the slurry residence time is 120 minutes. Step 4: The remaining steps are the same as in Example 1.
[0026] Example 4 1. Catalyst preparation steps Step 1: Take coal-based columnar activated carbon (Φ1.5mm), reflux with 15wt% nitric acid at 100℃ for 4 hours, wash with water until neutral, dry at 110℃ for 12 hours, and then activate with steam at 1200℃ for 110 minutes to obtain a hierarchical porous activated carbon carrier. The pore volume ratio is 78% for mesopores (2-50nm), 15% for macropores (>50nm), and the total pore volume is 1.25cm³. 3 / g; Step 2: Weigh out ferric nitrate and copper nitrate according to the Cu / (Fe+Cu) atomic molar ratio of 0.23, prepare a mixed aqueous solution with a total concentration of 0.5 mol / L, and impregnate it with an equal volume of the carrier obtained in Step 1, and let it stand at room temperature for 12 hours. Step 3: Calcination at 350℃ in air atmosphere for 2 hours, followed by calcination at 550℃ in nitrogen atmosphere for 3 hours, yielding a Fe-Cu bimetallic catalyst with a loading of 10.1wt%. XRD analysis showed that it contained CuFe2O4 spinel phase and CuO phase.
[0027] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Overall tower structure: total height 11.5m, inner diameter 1.8m, wall thickness 16mm; Forced oxidation zone: 4.6m high (accounting for 40% of the total height), umbrella-shaped pre-distributor with an umbrella surface angle of 60°, and a 10mm annular material drop gap reserved between the outer ring of the aeration plate and the tower wall; Insulated liquid distribution zone: 1.725m high (15% of the total height), the outer wall of the tower is wrapped with an 80mm thick aluminum silicate fiber insulation layer; the interior is equipped with 3 layers of annular V-shaped groove liquid distributors, with a cross-sectional angle of 75° and a groove depth of 15mm; from top to bottom, the diameter of the first layer of V-shaped grooves is 1.71m (95% of the tower diameter), the second layer is 1.45m (decreasing by 15%), and the third layer is 1.23m (decreasing by 15%); the vertical spacing between adjacent layers is 300mm; Fixed bed catalytic conversion zone: height 5.175m (accounting for 45% of the total height), wire mesh filter layer pore size 100μm, catalyst bed height 4.5m.
[0028] 3. System Operation Steps Step 1: The sulfur foam is separated by a super centrifuge (1700 r / min), and 35% of the clear liquid is sent to a concentration tower to concentrate to a total salt concentration of 520 g / L; Step 2: Concentrate the slurry at 2.5m 3A flow rate of / h is fed into the integrated reaction tower, with a forced oxidation zone temperature of 150℃, a pressure of 0.6MPa, and an excess air coefficient of 38%; Step 3: The slurry is evenly distributed through three layers of annular V-shaped grooves. The residence time in the adiabatic distribution zone is 30 seconds, and the temperature drops from 150℃ to 145℃, a temperature drop of 5℃. The temperature in the catalytic conversion zone is 80℃, the pressure is 0.06MPa, and the slurry residence time is 120 minutes. Step 4: The remaining steps are the same as in Example 1.
[0029] Comparative Example 1 1. Catalyst preparation steps Completely consistent with Example 1.
[0030] 2. Equipment Structure Independent oxidation tower: a vertical pressure vessel made of 316L stainless steel, 5m high and 1.8m inner diameter, with a slurry inlet and umbrella-shaped pre-distributor at the top, and an aeration plate at the bottom (parameters are the same as in Example 1). The outer wall is equipped with a steam jacket, and the bottom is equipped with a slurry outlet. It is connected to a plate heat exchanger through a DN150 stainless steel pipe, and a centrifugal pump, flow valve and pressure gauge are installed on the pipe. Plate heat exchanger: Model BR0.3-1.0-20, made of 316L stainless steel, used for cooling high-temperature slurry after oxidation, with a heat exchange area of 20m². 2 ; Independent catalytic conversion tower: a vertical pressure vessel made of 316L stainless steel, 6m high and 1.8m inner diameter, with a slurry inlet at the top (connected to the heat exchanger outlet pipe). Its internal structure is the same as that of the fixed bed catalytic conversion zone in Example 1 (including a wire mesh filter layer, catalyst bed, and porous support plate). The structure of the heat-insulating flow distribution zone is the same as that of Example 1 (4 layers of annular V-shaped grooves). Connection method: Bottom outlet of independent oxidation tower → pipeline → centrifugal pump → plate heat exchanger → top inlet of independent catalytic conversion tower. The total length of the pipeline is 15m, the diameter is DN150, and the outer wall of the pipeline is wrapped with a 50mm thick insulation layer.
[0031] 3. System Operation Steps Step 1: Sulfur foam pretreatment (centrifugation, concentration) is the same as in Example 1; Step 2: Concentrate the slurry at 2.5m 3 The slurry is fed into an independent oxidation tower at a flow rate of / h, with the temperature controlled at 135℃, the pressure at 0.48MPa, and the excess air coefficient at 38%. After the oxidation reaction is completed, the slurry is sent to a plate heat exchanger by a centrifugal pump and cooled to 65℃. Step 3: The cooled slurry is sent to the top of the independent catalytic conversion tower. After being evenly distributed through the adiabatic flow distribution zone (4 layers of annular V-shaped grooves), it enters the catalyst bed. The temperature of the catalytic conversion zone is controlled at 65℃, the pressure at 0.03MPa, and the slurry residence time is 100 minutes. Step 4: The remaining steps (pressure filtration, incineration to produce acid) are the same as in Example 1.
[0032] Comparative Example 2 1. Catalyst preparation steps Completely consistent with Example 1.
[0033] 2. Detailed structure of the integrated oxidation-catalysis reaction tower The forced oxidation zone and fixed-bed catalytic conversion zone have the same structure as in Example 1; Insulated flow distribution area: Replaced with a single conical flow guide plate made of 316L stainless steel, with the cone tip pointing downwards, a cone base diameter of 1.71m (95% of the tower body diameter), a cone tip diameter of 0.54m, and a cone angle of 65°. It is fixed to the inner wall of the tower body by welding with 4 supports. There are no other flow distribution structures below the flow guide plate. The insulation layer on the outer wall of the tower body is the same as in Example 1.
[0034] 3. System Operation Steps It is completely consistent with Example 1, except that the liquid distribution structure of the adiabatic liquid distribution area is different.
[0035] Comparative Example 3 1. Catalyst preparation steps Step 1: Take ordinary coal-based activated carbon (Φ1.5mm), without nitric acid reflux activation or steam activation treatment, and use it directly. Testing shows that the pore volume ratio is 52% for mesopores (2-50nm), 10% for macropores (>50nm), and the total pore volume is 0.85cm³. 3 / g; Step 2: Prepare a mixed aqueous solution of ferric nitrate and copper nitrate according to the atomic molar ratio of Cu / (Fe+Cu) of 0.30, and impregnate it with an equal volume of the ordinary activated carbon carrier obtained in Step 1, and let it stand at room temperature for 12 hours. Step 3: Calcination at 350℃ in air for 2 hours, followed by calcination at 550℃ in nitrogen for 3 hours to obtain the Fe-Cu bimetallic catalyst.
[0036] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Completely consistent with Example 1.
[0037] 3. System Operation Steps It is completely identical to Example 1, except for the catalyst support.
[0038] Comparative Example 4 1. Catalyst preparation steps Step 1: Take a graded porous activated carbon carrier (71% mesopores, 19% macropores) consistent with that in Example 1. Step 2: Weigh out only ferric nitrate and prepare an aqueous solution with a concentration of 0.5 mol / L. Impregnate the carrier obtained in Step 1 with an equal volume and let it stand at room temperature for 12 hours. Step 3: Calcination at 350℃ in air atmosphere for 4 hours to obtain a single Fe supported catalyst with an Fe loading of 8 wt%. XRD analysis showed that it contained only the Fe2O3 phase.
[0039] 2. Detailed structure of the integrated oxidation-catalysis reaction tower Completely consistent with Example 1.
[0040] 3. System Operation Steps Steps 1 to 2 and steps 4 to 6 are the same as in Example 1; Step 3: Increase the temperature of the catalytic conversion zone to 88℃, while keeping the other parameters unchanged.
[0041] Comparative Example 5 1. Catalyst preparation steps Completely consistent with Example 1.
[0042] 2. Detailed structure of the integrated oxidation-catalysis reaction tower The forced oxidation zone and fixed-bed catalytic conversion zone have the same structure as in Example 1; Insulated flow distribution area: No aluminum silicate fiber insulation layer, only the tower body itself is insulated, and the rest of the structure (4 layers of annular V-shaped grooves) is the same as in Example 1.
[0043] 3. System Operation Steps Completely identical to Example 1, except that the heat-insulating flow distribution area has no heat-insulating layer.
[0044] Comparative Example 6 1. Catalyst preparation steps Step 1: Take ordinary coal-based activated carbon (Φ1.5mm), without graded pore control, with mesopores accounting for 52%; Step 2: Weigh out only ferric nitrate, prepare an aqueous solution, impregnate an equal volume of the support obtained in Step 1, and calcine in air at 350°C for 4 hours to obtain a single Fe supported catalyst (Fe content 8wt%).
[0045] 2. Equipment Structure Independent oxidation tower: consistent with the independent oxidation tower in Comparative Example 1; Independent catalytic conversion tower: a vertical pressure vessel with a flat porous liquid distributor (5 mm pore diameter, 20 mm pore spacing) on the top, filled with the single Fe catalyst prepared in step 1, and the rest of the structure is the same as the independent catalytic conversion tower of Comparative Example 1. Connection method: Same as Comparative Example 1 (pipeline + heat exchanger connection).
[0046] 3. System Operation Steps Step 1: Sulfur foam pretreatment is the same as in Example 1; Step 2: The concentrated slurry is fed into an independent oxidation tower at a temperature of 135℃, a pressure of 0.48MPa, and an excess air coefficient of 38%. Step 3: After the oxidation slurry is cooled to 85°C by a heat exchanger, it is sent to an independent catalytic conversion tower, distributed by a plate porous distributor, and then enters the catalyst bed, where it stays for 100 minutes. Step 4: The remaining steps are the same as in Example 1.
[0047] Comparative Example 7 1. Catalyst preparation steps Completely consistent with Example 1.
[0048] 2. Detailed structure of the integrated oxidation-catalysis reaction tower The forced oxidation zone and fixed-bed catalytic conversion zone have the same structure as in Example 1; Insulated flow distribution area: 4 layers of annular V-shaped grooves with a cross-sectional angle of 65° and a groove depth of 12mm. The vertical spacing between adjacent layers is 250mm. From top to bottom, the diameter of the first layer of V-shaped grooves is 1.71m, the second layer is 1.54m (decreasing by 10%), the third layer is 1.38m (decreasing by 10%), and the fourth layer is 1.24m (decreasing by 10%). The rest of the structure is the same as in Example 1.
[0049] 3. System Operation Steps It is completely consistent with Example 1, except that the V-groove diameter decreases by a different percentage.
[0050] Performance verification 1. Each unit shall be operated continuously, and the system shall be shut down when any of the following conditions occur: ① Bed pressure drop increases by more than 200 kPa; ② Ammonium thiocyanate residue exceeds 2000 ppm; ③ Catalyst deactivation requires a temperature increase of more than 15°C to maintain conversion rate. 2. Take a sample of the effluent from the catalytic conversion zone every 24 hours. Determine the residual amount of ammonium thiosulfate using the iodometric method and the residual amount of ammonium thiocyanate using the formaldehyde method combined with spectrophotometry. Calculate the overall conversion rate. 3. Real-time metering of low-pressure steam consumption in the ammonium salt section, converted to "t / t ammonium sulfate" unit; 4. Record the bed pressure drop every 72 hours and calculate the final pressure drop increase; 5. After the operation is completed, determine the nitrogen recovery rate (based on the ratio of the total nitrogen in the raw material to the total nitrogen in the ammonium sulfate product). 6. Observe the scaling inside the equipment and record the location and severity of the scaling.
[0051] Performance verification results
[0052] Examples 1-4 (retaining all core technical features) all exhibit excellent comprehensive performance: comprehensive conversion rate ≥99.68%, continuous stable operation time ≥1920h, steam consumption ≤0.85t / t ammonium sulfate, nitrogen recovery rate ≥99.6%, and no obvious scaling phenomenon, proving that the parameter range defined in the claims (3~5 layers of V-shaped tank, diameter decreasing by 15~20%, catalyst porosity 63~78%, Cu ratio 0.23~0.37, etc.) is effective and optimal.
[0053] Comparative Examples 1-7 (without or with a single core technical feature replaced) all showed significant performance degradation: the split-tower structure (Comparative Example 1) resulted in heat loss and intermediate deactivation, with a continuous operating time of only 350 hours; the single conical guide plate (Comparative Example 2) could not distribute the liquid evenly, resulting in a decrease in both conversion rate and operating time; the ordinary carrier (Comparative Example 3) caused catalyst blockage, with a conversion rate of only 94.6%; the single Fe catalyst (Comparative Example 4) required heating to maintain conversion, increasing energy consumption by 30%; the lack of an insulation layer (Comparative Example 5) resulted in severe heat loss, with a nitrogen recovery rate of only 96.8%; the existing technology combination (Comparative Example 6) had the worst overall performance, with a continuous operating time of only 380 hours; the deviation in the V-groove diameter reduction ratio (Comparative Example 7) resulted in uneven liquid distribution, shortening the operating time to 1450 hours.
[0054] The above results fully demonstrate that the present invention possesses outstanding substantive features and significant progress.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A sulfur foam full-scale recovery and treatment system based on an integrated reaction tower, characterized in that, The system includes an integrated oxidation-catalysis reaction tower, which is a single vertical pressure vessel and consists of a forced oxidation zone, an adiabatic liquid distribution zone, and a fixed-bed catalytic conversion zone from top to bottom. The forced oxidation zone and the fixed bed catalytic conversion zone are connected only through the adiabatic flow distribution zone. The adiabatic flow distribution zone includes 3 to 5 layers of coaxially arranged annular V-shaped groove flow distributors. The cross-section of the annular V-shaped groove flow distributor is a V-shaped structure, and the annular diameter of each layer of annular V-shaped groove gradually decreases from top to bottom. This is used to gradually and evenly distribute the wall-adhering slurry falling from the forced oxidation zone towards the center of the tower body, so as to achieve uniform liquid distribution across the entire cross-section.
2. The system according to claim 1, characterized in that, The included angle of the V-shaped cross section of the annular V-shaped groove liquid distributor is 60-75°, and the groove depth is 8-15mm.
3. The system according to claim 1, characterized in that, The annular diameter of two adjacent annular V-shaped grooves decreases by 15% to 20% from top to bottom, and the projection of the groove opening of the lower annular V-shaped groove completely covers the projection of the groove bottom of the upper annular V-shaped groove.
4. The system according to claim 1, characterized in that, The vertical spacing between two adjacent layers of annular V-shaped groove liquid distributors is 200-300 mm, and the axis of all annular V-shaped grooves coincides with the axis of the reaction tower.
5. The system according to claim 1, characterized in that, The hierarchical porous activated carbon support filling the fixed bed catalytic conversion zone satisfies the following requirements: 63-78% of the pore volume is 2-50 nm mesopores, and 15-25% of the pore volume is >50 nm macropores.
6. The system according to claim 5, characterized in that, The hierarchical porous activated carbon support is loaded with Fe-Cu bimetallic oxide, and the atomic molar ratio of Cu to Fe, Cu / (Fe+Cu), is 0.23 to 0.
37.
7. The system according to claim 6, characterized in that, The Fe-Cu bimetallic oxide exists in the form of a coexistence of CuFe2O4 spinel phase and CuO phase.
8. The system according to claim 1, characterized in that, The forced oxidation zone is equipped with an aeration plate at the bottom. A 10-15mm annular material drop gap is reserved between the outer ring of the aeration plate and the inner wall of the reaction tower. The annular material drop gap is directly below the slot of the uppermost annular V-shaped groove guide liquid distributor.
9. The system according to claim 1, characterized in that, The outer wall of the tower body in the insulated flow distribution zone is wrapped with an insulation layer, and the residence time of the slurry in this zone is ≤30s and the temperature drop is ≤5℃.
10. A method for the full-scale recovery and treatment of sulfur foam based on an integrated reaction tower, characterized in that, Using the system described in any one of claims 1-9, a concentrated slurry containing ammonium thiosulfate and ammonium thiocyanate is added from the top of the forced oxidation zone. After oxidation by introducing air, the slurry falls through the annular material drop gap on the outer ring of the aeration plate into the uppermost annular V-shaped groove of the adiabatic guiding liquid distribution zone. After being gradually distributed to the center of the tower body through 3 to 5 annular V-shaped grooves with decreasing diameters, it flows evenly into the fixed bed catalytic conversion zone for catalytic conversion. After solid-liquid separation, the conversion liquid yields an ammonium sulfate solution, and the solid sulfur-containing substances are sent to the incinerator to produce acid.
Citation Information
Patent Citations
Treatment process of coking desulfurization by-product
CN114602299A